Identifying and Mapping Study of the Information Professional in Library with Scientometric Analysis - Kamaludin (Mr.) Kamaludin; Abdurrakhman Prasetyadi Abdurrakhman Prasetyadi (THE LIGHT : Journal of Librarianship and Information Science, 2022)
The development of information in the digital era forces librarians to change their roles to become information professionals who have modern skills to face challenges in the digital environment. This study aimed to determine the extent of the studies conducted on information professionals in libraries and to find out the themes and terms that were often used, the trend of topics each year, and the social networks of the authors. The method used was Scientometric analysis using a single search in the Lens.org database. Articles were searched using the terms “information professional” AND “library” in the title. The data obtained were 1523 publications from 1950 to 2020. The results of this study showed that in 2011 and 2014 the largest number of publications were 76 and 84 articles, respectively. In addition, the average growth rate related to publications among information professionals was quite high at 29% during the analyzed period. The study themes were divided into 4 major theme groups and the basic theme was the most frequently used. Then the term that most often appears was "information" with 1110 repetitions. There were also technical terms such as digital, application, and internet which indicate that the study of information professionals had adapted to systems in the digital era. Following the trend of topics in the third quarter (2013-2020), it showed more about the LIS and skills.